The Limits and Effects of Tort Liability and Civil Liability from an Analytical Point of View - Ezzat Abdel Rahim Shaker; Rawia Ghareeb Attia; Samir Adel Mustafa (International Journal of Law Research and Studies, 2024)
Civil liability is a legal obligation that arises from harm to others, whether as a result of a breach of contractual obligations or due to tortious acts and aims to compensate for the damage resulting from this breach. Tort liability for the actions of others is considered an essential part of the civil responsibility incurred by many individuals, and it is one of the most important topics of modern civil law that deserves research and study. It is influenced by the development of social thought prevailing in society, which changes according to different life circumstances. This responsibility is closely interconnected with daily life. It is characterized by its continuous practical application. The research presents the concepts, foundations, and cases of tort liability as part of civil liability. It attempts to present these topics through an analytical view and by application to several laws, including Egyptian law, Moroccan law, Algerian law, Iraqi law, and Saudi law.